Suicidal behaviors and depression “among adolescents in Hanoi, Vietnam: A multilevel analysis of data from the Youth Risk Behavior Survey 2019 - Nguyen Thi Khanh, Huyen (Health Psychol Open, 2020)
This study described the prevalence of suicidal behaviors and depression among adolescents in Hanoi, Vietnam, and examines the associated factors. In 2019, a school-based survey was conducted in three high schools in Hanoi and 661 high students were included into the study. We found that the prevalence of 12-month suicidal thoughts, suicide plans, and suicide attempts were 14.2%, 5.5%, and 3.0% respectively. Notably, the depression score mean was 16.1±4.9, among major predictors of suicidal ideation. Therefore, developing psychological care services in school is imperative to the early detection of mental disorders and the prevention of suicidal behaviors for the students.